Correlations between histology and neuronal activity recorded by microelectrodes implanted chronically in the cerebral cortex. (25th April 2016) - McCreery, Douglas; Cogan, Stuart; Kane, Sheryl; Pikov, Victor
Abstract: Objective. To quantify relations between the neuronal activity recorded with chronically-implanted intracortical microelectrodes and the histology of the surrounding tissue, using radial distance from the tip sites and time after array implantation as parameters. Approach. 'Utah'-type intracortical microelectrode arrays were implanted into cats' sensorimotor cortex for 275–364 days. The brain tissue around the implants was immuno-stained for the neuronal marker NeuN and for the astrocyte marker GFAP. Pearson's product-moment correlations were used to quantify the relations between these markers and the amplitudes of the recorded neuronal action potentials (APs) and their signal-to-noise ratios (S/N). Main results. S/N was more stable over post-implant time than was AP amplitude, but its increased correlation with neuronal density after many months indicates ongoing loss of neurons around the microelectrodes. S/N was correlated with neuron density out to at least 140 μ m from the microelectrodes, while AP amplitude was correlated with neuron density and GFAP density within ∼80 μ m. Correlations between AP amplitude and histology markers (GFAP and NeuN density) were strongest immediately after implantation, while correlation between the neuron density and S/N was strongest near the time the animals were sacrificed. Unlike AP amplitude, there was no significant correlation between S/N and density of GFAP around the tip sites. Significance . Our findings indicate an evolving interaction between changes in the tissue surrounding the microelectrodes and the microelectrode's electrical properties. Ongoing loss of neurons around recording microelectrodes, and the interactions between their delayed electrical deterioration and early tissue scarring around the tips appear to pose the greatest threats to the microelectrodes' long-term functionality.